PERTUMBUHAN BIBIT KELAPA SAWIT YANG DIBERI TRICHOKOMPOS DENGAN FREKUENSI BERBEDA PADA PEMBIBITAN UTAMA - Meiza ' Arnanda; Muhammad ' Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
ABSTRACT The experiment aims to determine the effect of application with different frequency of Trichocompost on the growth of seedlings of oil palm (Elaeis guineensis Jacq.) and gain the best frequency of Trichocompost for the growth of oil palm seedlings in the main nursery stage. This research was conducted at the Agriculture Experiment Station of Agriculture Faculty University of Riau, from April to August 2015. The treatment were consisted of 4 frequencies, ie: without giving Trichocompost (F0), Trichocompost given one time (F1), Trichocompost given two times (F2) and Trichocompost given three times (F3) that repeated 4 times. Data were analyzed using analysis of variance followed by Duncan's multiple range test at 5% level. Parameters measured were: seedling height (cm), number of leaves (leaf), stump diameter (cm), the ratio of the canopy root dry weight (g) and root volume (cm3). The result of the research showed that frequencies of Trichocompost significantly affected on plant height and plant dry weight, but not significantly effect on the number of leaves, hump diameter and canopy ratio of root volume. Trichocompost given three times tended to give a better effect on seedling height (73.02 cm) and seedling dry weight (83.07 g). Keywords: oil palm, Trichocompost, frequency.